KEARIFAN LOKAL DALAM UMPASA BATAK TOBA - Ismarini Hutabarat; Lia Khalisa (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2019)
Researches on cultural tradition showed that cultural tradition contained various cultural values and norms as the heritage of the forefathers which were based on the functions in organizing the social life of the society could be classified as local wisdom. This research did not analyze the data based on sample or population. It was done this way because the object studied were the elements of kinds of local wisdom found in the umpasa of Toba Batak which were conveyed in marriage ceremony in Toba Batak culture. Therefore, this research was known as case study because the object of the study was only based on certain phenomena. In analyzing the data, the researcher applied descriptive method. This method not only focused on collecting and arranging the data but also the analysis and interpretation of the data analyzed. The result of the study showed that the local wisdoms that could be used to increase the people’s prosperity in the umpasa conveyed in marriage ceremony in Toba Batak culture were the values of hard working, discipline, education, health, mutual cooperation, gender management and the preservation and creativity of culture. It was expected that Toba Batak society, especially Toba Batak youths, keep preserving umpasa of Toba Batak so that they could apply the local wisdoms contained in the umpasa in their daily life.